Exploring environment as cross-cutting issue among Humanitarian-Development Nexus Actors (American Journal of Agricultural Science, Engineering, and Technology, 2021)
Environment mainstreaming across the humanitarian operations and long-term development programs is imperative to the new way of working agreed in the World Humanitarian Summit (2016). Mainstreaming environment in Humanitarian-Development nexus is crucial to minimize the environmental impacts of humanitarian projects and to build long term resilience against environmental and climatic risks and vulnerabilities of communities. This study explores the current environmental mainstreaming strategies of humanitarian and development organizations at the institutional and operational level based on specific attributes. This study conducts the case study of leading humanitarian and development organizations, namely, WFP, IFRC, UNDP, and USAID, based on the conceptual framework on mainstreaming strategies derived from various literature. Multiple case study approach was employed based on information collected through various secondary sources and personal consultation with the organizations. The finding of this study signifies the presence of varying environmental mainstreaming practices within the studied organizations, and comparative analysis among them is also presented. Finally, this study suggests that joint contextual environmental (and climate) analysis by humanitarian and development actors and inclusion of environmental consideration in collaborative multi-year programming to minimize environmental damage in protracted crises.